Development and evaluation of the evidence‐based practice classroom observation measure (EBP‐COM). (8th March 2019) - Paff, Madison L.; Trump, Cary E.; Wunderlich, Kara L.; Harrison, Ashley J.; Ayres, Kevin M.
Abstract : Due to the increased emphasis on evidence‐based practices (EBPs) in recent education initiatives, classroom observers need an objective way to measure teacher use of EBPs. Although some measures for this purpose exist, these measures are limited by their reliance on self‐report. Therefore, we created a direct observation tool titled the Evidence‐Based Practice Classroom Observation Measure (EBP‐COM) for observers to assess the use of EBPs by teachers of students with autism spectrum disorder (ASD). We evaluated reliability and validity of the EBP‐COM, as well as whether the assessment tool could detect change in teacher behavior. A measurement refinement process involving six raters collecting 65 data points revealed the EPB‐COM to have sound psychometric properties. With this tool, researchers can conduct comprehensive and objective assessments of teacher EBP use.